The Influence of Work Environment and Work Motivation with Teacher Performance at Madrasah Aliyah Negeri 1 Palembang - Chrisman Z, Achmad; Lian, Bukman; Putra, Alhadi Yan (Jurnal Pendidikan Tambusai, 2021)
The goal of this study is to demonstrate the impact of the work environment on teacher performance, to demonstrate the impact of work motivation on teacher performance, and to demonstrate the impact of the work environment and work motivation on teacher performance together. At Madrasah Aliyah Negeri 1, Palembang, this study was carried out. The problems that exist include the frequent occurrence of confusion between teachers in performing their duties, resulting in the less favorable working atmosphere of the teacher, unsatisfactory student output could be attributable to the standard of teacher work that has not been maximized because the motivation of teachers to work is still poor, In implementing policies, there are often differences of opinion between teachers and the principal of madrasah, lack of guidance for teachers that leads to low teacher morale, the absence of teacher imagination in creating independent material still depends on the books used, teachers often arrive late or come home not yet that can harm learning students. Observations, questionnaires, and documentation were used to collect data. The study carried out was an analysis of the association between the t – test and the F – test. The findings of the analysis of the data collected were that the working environment had an effect on the performance of teachers in Madrasah Aliyah Negeri 1 Palembang. There is an influence on the success of teachers in Madrasah Aliyah Negeri 1 Palembang by Job Motivation. The work climate and work motivation together have an effect on the teacher performance in Madrasah Aliyah Negeri 1 Palembang.